2023
DOI: 10.3390/microorganisms11040892
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Growth and Removal of Pseudomonas Biofilms on Cellulose-Based Fabrics

Abstract: Biofilms are often tolerant towards routine cleaning and disinfection processes. As they can grow on fabrics in household or healthcare settings, resulting in odors and serious health problems, it is necessary to contain biofilms through eradication strategies. The current study proposes a novel test model for the growth and removal of biofilms on textiles with Pseudomonas fluorescens and the opportunistic nosocomial pathogen Pseudomonas aeruginosa as model organisms. To assess the biofilm removal on fabrics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…For this purpose, it is demonstrated that dehydrated Pseudomonas protegens (PP) BFs behave as rigid films, where energy dissipation is negligible, thus validating the conditions for using the Sauerbrey equation to determine the percentage of enzymatic removal. This allows applying a simplified measuring protocol and data treatment, in comparison with applications of QCM-D in flow cell viscoelastic models for BF removal studies. , P. protegens, a microorganism of relevance in microbial induce corrosion processes, was selected for testing the developed approach. , A selection of enzymes, targeting the different components of the BF matrix and/or bacteria cells, was evaluated for removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, it is demonstrated that dehydrated Pseudomonas protegens (PP) BFs behave as rigid films, where energy dissipation is negligible, thus validating the conditions for using the Sauerbrey equation to determine the percentage of enzymatic removal. This allows applying a simplified measuring protocol and data treatment, in comparison with applications of QCM-D in flow cell viscoelastic models for BF removal studies. , P. protegens, a microorganism of relevance in microbial induce corrosion processes, was selected for testing the developed approach. , A selection of enzymes, targeting the different components of the BF matrix and/or bacteria cells, was evaluated for removal.…”
Section: Introductionmentioning
confidence: 99%
“…This allows applying a simplified measuring protocol and data treatment, in comparison with applications of QCM-D in flow cell viscoelastic models for BF removal studies. 34 , 40 P. protegens , a microorganism of relevance in microbial induce corrosion processes, was selected for testing the developed approach. 41 , 42 A selection of enzymes, targeting the different components of the BF matrix and/or bacteria cells, was evaluated for removal.…”
Section: Introductionmentioning
confidence: 99%